How Teacher leadership in increasing student learning motivation in Islamic Education, why must be conducted? - Selvia Zuni Murningsih; Purwanto, Nurtanio Agus; Ikhwan, Muh. Saidil (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
Students' motivation plays a fundamental role in enhancing their academic performance, which is particularly true in Islamic education. Students with high motivation are likelier to engage actively with the learning material, retain knowledge, and demonstrate improved outcomes. One key factor in cultivating this motivation is the leadership provided by teachers in the classroom. Therefore, this research aims to determine teacher leadership strategies to increase student learning motivation at one Islamic education centre in East Lombok. This research is qualitative research and a phenomenological perspective that focuses on teacher leadership. The subjects of this research were two teachers and four students at one Islamic education in East Lombok. The research was carried out at an Islamic education centre in East Lombok. Interviews and documentation are data collection techniques used in this research. The results of this research show that the teacher's leadership strategy in increasing student learning motivation is by being a good listener, encouraging students to be more active in class, using the right learning method, fulfilling students' learning needs, time discipline, and being a role model in class. The study results imply that teachers, with their learning leadership, can increase student learning motivation.